2008
DOI: 10.1249/mss.0b013e318163744a
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Preconditioning Protects against Doxorubicin-Induced Cardiac Dysfunction

Abstract: Endurance training prior to DOX treatment protects against acute DOX cardiotoxicity for up to 10 d, and this protection can potentially be explained by a preservation of MHC isoform distribution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
104
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(113 citation statements)
references
References 33 publications
6
104
3
Order By: Relevance
“…This is a heat shock protein (HSP) found in cardiomyocytes in exercise, and increased HSP72 levels are associated with preservation of cardiac functions during oxidative stress. 17 Wonders et al 14 observed that the acute effect of exercise prevented the decrease of cardiac function at this dose. Martins et al 24 investigated the protective effect against DNA damage in cardiac cells in male rats receiving DOX, and obtained a positive result.…”
Section: Treatment Protocolsmentioning
confidence: 86%
See 2 more Smart Citations
“…This is a heat shock protein (HSP) found in cardiomyocytes in exercise, and increased HSP72 levels are associated with preservation of cardiac functions during oxidative stress. 17 Wonders et al 14 observed that the acute effect of exercise prevented the decrease of cardiac function at this dose. Martins et al 24 investigated the protective effect against DNA damage in cardiac cells in male rats receiving DOX, and obtained a positive result.…”
Section: Treatment Protocolsmentioning
confidence: 86%
“…22,23 Four studies used a single dose of 15 mg/kg. 13,14,19,24 In the study by Chicco et al, 13 exercise attenuated cardiac dysfunction and lipid peroxidation induced by DOX, and increased HSP72 levels. This is a heat shock protein (HSP) found in cardiomyocytes in exercise, and increased HSP72 levels are associated with preservation of cardiac functions during oxidative stress.…”
Section: Treatment Protocolsmentioning
confidence: 96%
See 1 more Smart Citation
“…Although, there is evidence that acute exercise resulted in oxidative stress and cardiac damage (Teixeira de Lemos et al, 2011), it seems probable that regular endurance exercise training could constitute an excellent tool either to prevent and/or to treat several diseases. Also, while most recent studies have focused on the treatment effect of endurance exercise in induce DOX cardiotoxicity (Hydock et al, 2008;Kavazis et al, 2010;Ascensão et al, 2012). We are the first to investigate the cardioprotective effects of prior (pretreatment) short-term treadmill running endurance exercise on doxorubicininduced cardiotoxicity with various dosages (10 and 20 mg/kg) of the DOX drug in heart tissue.…”
Section: Is Short-term Exercise a Therapeutic Tool For Improvement Ofmentioning
confidence: 99%
“…The preventive and pretreatment role of regular endurance exercise as an antioxidant factor on HSP 70 in heart has not been sufficiently studied. Also, while most recent studies have focused on the treatment effect of endurance exercise in induce DOX cardiotoxicity Hydock et al, 2008;Kavazis et al, 2010;Ascensão et al, 2011). We are the first to investigate the cardioprotective effects of prior (pretreatment) treadmill running endurance exercise on HSP 70 and doxorubicin-induced cardiotoxicity with various dosages.…”
Section: Pretreatment Effect Of Running Exercise On Hsp 70 and Doxindmentioning
confidence: 99%